KONTRIBUSI KEKUATAN OTOT LENGAN, KECEPATAN LARI 50 METER DAN KETEPATAN MELEMPAR TERHADAP KETERAMPILAN BERMAIN KASTI - Hasruddin Hasruddin (STKIP Paris Barantai, 2019)
This research is a type of descriptive research. The population is students of SDN 1 Sungai Pasir, Kotabaru Regency. The sample used is some students in grade V and VI SDN 1 Sungai Pasir, Kotabaru Regency, as many as 30 students. The technique of determining the sample is by random selection by lottery (Simple Random Sampling). The data analysis technique used is descriptive analysis and inferential analysis through the SPSS 24.00 program with a significance level of 5% or Î± = 0.05. The results showed that; there was a significant contribution to the strength of arm muscle, to the playing skill of students of SDN 1 Sungai Pasir, Kotabaru Regency 61.1%, there was a significant contribution between the speed of running 50 meters to the playing skills of students of SDN 1 Sungai Pasir, Kotabaru Regency by 61.5%, there was a significant contribution of the accuracy of throwing to the baseball skill of SDN 1 Sungai Pasir, Kotabaru Regency by 71.9%. there was a significant correlation between arm muscle strength, running speed of 50 meters and accuracy of throwing to the baseball skill of students at SDN 1 Sungai Pasir, Kotabaru Regency, by 59.6%. Keywords: Arm muscle strength, Running speed of 50 meters, Accuracy of throwing, Baseball skills